Distribution of virulence factors in pathogenic Escherichia coli isolates from diarrheal piglets and their antibacterial resistance - ZHANG Jing; JIANG Zhongqi; YU Huizhen; WU Yongfu; JIANG Mingjun (浙江大学学报. 农业与生命科学版)
Diarrhea in pre-weaning and post-weaning piglets is still a frequently occurring disease on scaled farms, and result in great economic losses. Enterotoxigenic Escherichia coli (ETEC) is a major cause, and the virulence factors are the key to its pathogenicity. The traditional and commonly detected pili of ETEC are F4 (K88), F5(K99), F6(987P), F18 and F41, and the enterotoxins include heat-stable STa and STb, heat-labile enterotoxin LT and Stx2e. However, new reports have shown that ETEC strains lacking of recognized fimbriae are becoming increasingly common, which may be linked to the use of vaccines incorporating fimbriated strains, providing selection pressure for the acquisition and carriage of novel, unrecognized virulence genes. Recently, EAST1 (enteroaggregative Escherichia coli heat-stable enterotoxin 1), PAA (porcine attaching and effacing-associated factor), AIDA-I (adhesin involved in diffuse adherence) and intimin encoded by eae (Escherichia coli attaching and effacing) have been reported. Nevertheless, few related data have been available in China; furthermore, the prevention strategies have been devised largely based on the virulence factors. In order to gain more insight into the pathogenesis of colibacillosis in piglets and control the disease, it is of significant importance to track the changes of E. coli virulence factors and antimicrobial resistance, and elucidate the possible relationship between them.Samples were collected by rectum swabs from diarrheal piglets on intensive pig farms of Zhejiang Province. A total of 124 pathogenic isolates were obtained after bacteria isolation, purification, and identification based on the combination of morphology and PCR techniques. The virulence factors were verified by PCR with specific primer pairs. Susceptibility testing was carried out by K-B method, and analyzed by Whonet software. The correction between antibacterial resistance and virulence factors was evaluated by Logistic regression analysis.The PCR results showed that fimbriae positive (F4+ and F41+) amounted to 7.26%(9/124). EAST1, PAA and AIDA-I were detected for the first time in the region. EAST1 turned out to be as high as 19.68%(24/124) of the isolates, whereas only 4.84%(6/124) and 2.42%(3/124) of the isolates harbored PAA and AIDA-I, respectively. Isolates were highly resistant to oxacillin (100%), co-trimoxazole (97.6%), rifampicin (97.6%), doxycycline (96%), carbenicillin (93.5%), ampicillin (93.5%) and amoxicillin (93.5%). In addition, streptomycin showed serious cross-resistance with ampicillin (75.45%), enrofloxacin (65.45%), gentamicin (78.18%), doxycycline (96%) and florfenicol (50.91%). Besides, all isolates were multi-drug resistant among them, the majority were resistant to 14-16 antibacterial agents (43.31%). Moreover, virulence factor eae was found to be corrected with amoxicillin/clavulanic acid (P=0.046) and doxycycline (P=0.020) resistance, respectively. Similarly, there was a significant correction between EAST1 and polymyxin B (P=0.004), EAST1 and chloramphenicol (P=0.013), respectively.This investigation demonstrated that prevalent virulence factors had largely changed compared with previous studies, and resistance was still on the increase, furthermore, there existed a correlation between them. Further research is required to better understand the complicated virulence factors, bacterial resistance and its subtle correction.